A variational approach with embedded roughness for adhesive contact problems. Issue 20 (15th October 2020) - Paggi, Marco; Reinoso, José
Abstract: A new variational formulation is proposed for the solution of contact problems for profiles of arbitrary shape indenting a deformable half-plane, with special focus on rough indenters. The method exploits the new idea of accounting for the shape of roughness as a correction to the normal gap function. The resulting interface finite element with eMbedded Profile for Joint Roughness (MPJR interface finite element) is derived and its implementation is comprehensively described. The method is applied to a range of contact problems very challenging for traditional methods, opening new perspectives for the solution of contact problems with roughness and adhesion.